Intermediality and cultural assessment: digital flows in the global age, a review of Digital humanities and the study of intermediality in comparative cultural studies - Pinto, Isabel (2015)
A review of Digital Humanities and the Study of Intermediality in Comparative Cultural Studies, edited by Steven Tötösy de Zepetnek. Purdue Scholarly Publishing Services, 2013, 375 pp